Building a comprehensive team for the longitudinal care of single ventricle heart defects: Building blocks and initial results. (26th July 2017) - Texter, Karen; Davis, Jo Ann M.; Phelps, Christina; Cheatham, Sharon; Cheatham, John; Galantowicz, Mark; Feltes, Timothy F.
Abstract: Introduction: With increasing survival of children with HLHS and other single ventricle lesions, the complexity of medical care for these patients is substantial. Establishing and adhering to best practice models may improve outcome, but requires careful coordination and monitoring. Methods: In 2013 our Heart Center began a process to build a comprehensive Single Ventricle Team designed to target these difficult issues. Results: Comprehensive Single Ventricle Team in 2014 was begun, to standardize care for children with single ventricle heart defects from diagnosis to adulthood within our institution. The team is a multidisciplinary group of providers committed to improving outcomes and quality of life for children with single ventricle heart defects, all functioning within the medical home of our heart center. Standards of care were developed and implemented in five target areas to standardize medical management and patient and family support. Under the team 100 patients have been cared for. Since 2014 a decrease in interstage mortality for HLHS were seen. Using a team approach and the tools of Quality Improvement they have been successful in reaching high protocol compliance for each of these areas. Conclusions: This article describes the process of building a successful Single Ventricle team, our initial results, and lessons learned. Additional study is ongoing to demonstrate the effects of these interventions on patient outcomes.